Modern religious newspaper: forms of christian values actualization - Zoryana Procenko (Волинський благовісник, 2019)
The article sheds light on forms of Christian values actualization in interconfessional Christian newspapers in the face of the Russo-Ukrainian conflict in XXI century. In addition, the article is an analysis of Ukrainian religious editions in order to create a unique newspaper. Recommendations based on domestic and foreign experience compiled for the quality filling of such an interconfessional newspaper.